Nouvelles formes galéniques de thérapie ciblée en oncologie et l'apport de la pharmacie galénique - ZOUAOUI, Anissa Dikra; SAHRAOUI, Feriel; Dellali, Nihad; SAHRAOUI , Feriel ( Encadrant ) (Université Sétif 1 Ferhat Abbas, Faculté de Médecine, Département de Pharmacie, 2025)
Introduction : Cancer remains the second leading cause of death worldwide, representing a major therapeutic challenge. Faced with the limitations of conventional chemotherapies, targeted therapy has emerged as a revolutionary approach, necessitating the development of new galenic approaches aimed at improving action specificity, bioavailability, and reducing side effects. This work aims to evaluate the development of these targeted molecules and galenic innovations through a systematic literature review. Materials and Methods: This systematic review was conducted based on an exhaustive bibliographic search across six databases: Google Scholar, PubMed, ScienceDirect, Elsevier, Studymarter, and SpringerLink. Out of 98 identified articles, 57 were selected according to rigorous inclusion and exclusion criteria. The extracted data focused on the types of targeted therapies, the contribution of pharmaceutical compounding and galenic innovations, as well as encountered economic, regulatory, and environmental constraints. Results : Analysis of the articles highlighted trends in the development of new molecules for targeted therapy, including tyrosine kinase inhibitors, monoclonal antibodies, PARP inhibitors, antibody-drug conjugates, and more. Furthermore, recent advances in pharmaceutical compounding for the design of new forms such as nanoparticles, liposomes, and controlled-release systems were identified. These approaches aim to improve biocompatibility by limiting accumulation in the body, ensure controlled and prolonged release, guarantee the stability of active pharmaceutical ingredients (APIs), and reduce adverse effects and systemic toxicity. However, several obstacles to the adoption of these innovations were identified at the economic, regulatory, biological, and technological levels. Conclusion : At the end of this work, we conclude that these innovations in pharmaceutical compounding are essential for overcoming the challenges of targeted therapies, offering promising prospects for safer, more effective, and better-tolerated anticancer treatments. Keywords : Cancer, targeted therapy, pharmaceutical compounding, innovation, controlled release, regulatory challenges.
مقدمة: يظل السرطان السبب الثاني للوفاة عالمياً، ويشكل تحدياً علاجياً كبيراً. في مواجهة حدود العلاجات الكيميائية التقليدية، برزت العلاجات المستهدفة كنهج ثوري، مما استدعى تطوير طرق جاليانية جديدة تهدف إلى تحسين خصوصية الفعل، التوافر البيولوجي، وتقليل الآثار الجانبية. يهدف هذا العمل إلى تقييم تطور هذه الجزيئات المستهدفة والابتكارات الجاليانية من خلال مراجعة منهجية للأدبيات. المواد والطرق: أُجريت هذه المراجعة المنهجية بناءً على بحث شامل في ست قواعد بيانات: Google Scholar، PubMed، ScienceDirect، Elsevier، Studymarter وSpringerLink. من بين 98 مقالة تم تحديدها، تم اختيار 57 وفق معايير إدخال واستبعاد صارمة. استُخلصت البيانات حول أنواع العلاجات المستهدفة، دور الصيدلة الجاليانية والابتكارات الجاليانية، بالإضافة إلى التحديات الاقتصادية والتنظيمية والبيئية. النتائج: أبرز تحليل المقالات الاتجاهات في تطوير الجزيئات الجديدة في العلاج المستهدف (مثبطات كيناز التيروسين، الأجسام المضادة وحيدة النسيلة، مضادات PARP، اقتران الأجسام المضادة بالأدوية، وغيرها). كما تم تسليط الضوء على التقدمات الحديثة في الصيدلة الجاليانية لتصميم أشكال جديدة مثل الجسيمات النانوية، الليبوزومات وأنظمة الإطلاق المتحكم فيه. تهدف هذه الأساليب إلى تحسين التوافق الحيوي من خلال الحد من التراكم في الجسم، ضمان إطلاق متحكم ومطول، الحفاظ على استقرار المادة الفعالة، وتقليل الآثار الضارة والسمية الجهازية. مع ذلك، تم تحديد عدة عوائق لاعتماد هذه الابتكارات على المستويات الاقتصادية والتنظيمية والبيولوجية والتكنولوجية . الخاتمة: في نهاية هذا العمل، نستنتج أن هذه الابتكارات في الصيدلة الجاليانية ضرورية لتجاوز تحديات العلاجات المستهدفة، مما يفتح آفاقاً واعدة لعلاجات مضادة للسرطان أكثر أماناً وفعالية وتحملًا أفضل. الكلمات المفتاحية: السرطان، العلاج المستهدف، الصيدلة الجاليانية، الابتكار، الإطلاق المتحكم فيه، التحديات التنظيمي
Keywords: Cancer; Thérapie ciblée; Pharmacie galénique; Innovation; Libération contrôlée; Défis réglementaires